Method for in-situ construction of wide-range wavelength visible / ultraviolet titanium dioxide-sodium titanate and titanium dioxide-tungsten trioxide dual heterostructure on titanium surface
By constructing a double heterostructure of wide-domain wavelength visible/ultraviolet titanium dioxide @ sodium titanate and tungsten trioxide on the titanium surface, the existing TiO2 photocatalysts have poor degradation ability and inrecoverability in wastewater treatment, and efficient photocatalytic degradation and structural stability are achieved.
Patent Information
- Application Number
- CN202411739921.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing TiO2 photocatalysts have poor degradation capabilities in wastewater treatment and cannot be recycled and reused.
The double heterostructure with wide-domain wavelength visible/ultraviolet titanium dioxide @ sodium titanate and tungsten trioxide are constructed in situ by in-situ on the titanium surface, and a dual heterostructure with excellent photocatalytic effects is formed using microarc oxidation, microwave hydrothermal, ion deposition exchange and decrystallization technologies.
A photocatalyst with high catalytic effects in the visible and ultraviolet wavelength ranges is achieved, which improves the degradation rate of organic dyes in wastewater, and has a stable heterostructure, supporting long-term degradation performance.
Smart Images

Figure CN119549142A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for constructing a double heterostructure. Background Art
[0002] Currently, the commonly used photocatalysts are difficult to recycle or have a low recovery rate in the sewage treatment process, and the commonly used photocatalysts are TiO 2 The catalyst, usually nanomaterials, is mixed with sewage and degraded under light. Therefore, it is impossible to separate the catalyst from the sewage and reuse it to reduce the cost of sewage treatment. 2 Since the energy band gap is too wide, it can only absorb light in the ultraviolet band, and the recombination rate of photogenerated electrons and holes is high, which seriously affects the catalytic performance of the photocatalyst. Summary of the invention
[0003] The present invention aims to solve the existing TiO 2 Photocatalysts have poor degradation capabilities for organic dye wastewater and cannot be recycled and reused. Thus, a method for in situ construction of wide-range wavelength visible / ultraviolet light titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide dual heterostructures on a titanium surface is provided.
[0004] A method for in-situ construction of wide-band wavelength visible / ultraviolet titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide double heterostructures on a titanium surface, which is carried out in the following steps:
[0005] 1. Micro-arc oxidation treatment:
[0006] The titanium plate with the oxide layer removed is placed in an electrolyte, with the titanium plate with the oxide layer removed as an anode and the stainless steel plate as a cathode, and micro-arc oxidation is performed in a pulse constant current mode under the conditions of a current of 0.2A to 2.0A, a pulse frequency of 600Hz to 1000Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20°C to 30°C to obtain a titanium plate treated with micro-arc oxidation;
[0007] The electrolyte is composed of phosphate, fluoride salt, alkali solution and deionized water;
[0008] 2. Microwave hydrothermal treatment:
[0009] The titanium plate treated by micro-arc oxidation is immersed in an alkali solution for microwave hydrothermal treatment to obtain a titanium plate treated by microwave hydrothermal treatment;
[0010] 3. Ion deposition exchange treatment:
[0011] ① Immerse the titanium plate after microwave hydrothermal treatment in a tungstate solution, take it out and immerse it in hydrochloric acid, and finally wash it;
[0012] ② Repeat step 3① for 5 to 20 times, and obtain the titanium plate after ion deposition and exchange after drying;
[0013] 4. De-crystallization treatment:
[0014] The titanium plate after ion deposition exchange is placed in a muffle furnace and de-crystallized in an air atmosphere, thereby completing the in-situ construction of a wide-band wavelength visible / ultraviolet light titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide dual heterostructure on the titanium surface.
[0015] The beneficial effects of the present invention are:
[0016] The present invention aims to prepare in situ titanium dioxide / sodium titanate and / titanium dioxide@tungsten trioxide dual structures with excellent photocatalytic effect in the visible light and ultraviolet light wavelength bands on the titanium plate surface. A porous coating is prepared on the titanium plate surface by micro-arc oxidation technology, and then microwave hydrothermal treatment is performed to form a large number of sodium titanate nanowires (Na + +TiO 2 +OH - ―Na 0.23 TiO 2 ), providing more active sites for the subsequent deposition of tungstate ions; and then transformed into a composite structure of titanate and tungstate through ion deposition exchange technology, and then transformed into TiO 2 / WO 3 Heterogeneous structure; at the same time, the process parameters of ion exchange are controlled to retain the structure of sodium titanate nanowires and form TiO 2 / Na 0.23 TiO 2 Heterogeneous structure, thus achieving wide-range wavelength visible / ultraviolet light high catalytic performance, solving the existing TiO 2 The photocatalytic degradation rate of the photocatalyst is low and the recovery is difficult.
[0017] The sample treated by the present invention was tested by EDS spectrum. Tungsten was successfully introduced into the sample. The composition mainly consisted of W, Ti, O and Na. After XRD diffraction test, TiO 2 、Na 0.23 TiO 2 and WO 3 Phase. Scanning electron microscopy shows that a large amount of titanium dioxide @ sodium titanate and / titanium dioxide @ tungsten trioxide double heterostructures are formed on the surface. In addition, according to transmission electron microscopy photos, WO 3 Particles and TiO 2The nanorods have a good coupling relationship. The surface of the sample treated by the present invention is characterized for its photocatalytic ability. When placed in a methylene blue solution and irradiated by a xenon lamp, the degradation rate of the organic dye in the fifth cycle reaches more than 86%, and after 5 cycles of cycle testing, the heterogeneous structure on the scanning electron microscope photo does not undergo obvious changes, indicating that the sample obtained by the present invention has stable and long-term degradation performance.
[0018] Attached Notes
[0019] Figure 1 This is a scanning electron microscope image of the titanium dioxide / sodium titanate heterostructure constructed in situ on the titanium surface in step 2 of Example 1;
[0020] Figure 2 In-situ construction of wide-range wavelength visible / ultraviolet EDS spectrum of titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures on titanium surface in Example 1;
[0021] Figure 3 XRD spectrum of wide-range wavelength visible / ultraviolet titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide dual heterostructures in situ constructed on titanium surface in Example 1, A is anatase peak, B is titanium peak, C is rutile peak, D is tungsten oxide peak, and E is sodium titanate peak;
[0022] Figure 4 This is a scanning electron microscope image of the in-situ construction of wide-range wavelength visible / ultraviolet titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures on the titanium surface in Example 1;
[0023] Figure 5 This is a transmission electron microscopy image of a titanium dioxide @ tungsten trioxide heterostructure in the in-situ construction of a wide-range wavelength visible / ultraviolet titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructure on a titanium surface in Example 1;
[0024] Figure 6 The fifth cycle photocatalytic degradation rate diagram of the titanium plate after micro-arc oxidation treatment prepared in step 1 of Example 1 and the titanium surface in-situ constructed with wide-band wavelength visible / ultraviolet light titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructure;
[0025] Figure 7 This is a scanning photograph of the in-situ construction of wide-range wavelength visible / ultraviolet titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures on the titanium surface of Example 1 after five-cycle cyclic testing. DETAILED DESCRIPTION
[0026] Specific implementation method 1: This implementation method is a method for in-situ construction of a wide-range wavelength visible / ultraviolet titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructure on a titanium surface, which is carried out in the following steps:
[0027] 1. Micro-arc oxidation treatment:
[0028] The titanium plate with the oxide layer removed is placed in an electrolyte, with the titanium plate with the oxide layer removed as an anode and the stainless steel plate as a cathode, and micro-arc oxidation is performed in a pulse constant current mode under the conditions of a current of 0.2A to 2.0A, a pulse frequency of 600Hz to 1000Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20°C to 30°C to obtain a titanium plate treated with micro-arc oxidation;
[0029] The electrolyte is composed of phosphate, fluoride salt, alkali solution and deionized water;
[0030] 2. Microwave hydrothermal treatment:
[0031] The titanium plate treated by micro-arc oxidation is immersed in an alkali solution for microwave hydrothermal treatment to obtain a titanium plate treated by microwave hydrothermal treatment;
[0032] 3. Ion deposition exchange treatment:
[0033] ① Immerse the titanium plate after microwave hydrothermal treatment in a tungstate solution, take it out and immerse it in hydrochloric acid, and finally wash it;
[0034] ② Repeat step 3① for 5 to 20 times, and obtain the titanium plate after ion deposition and exchange after drying;
[0035] 4. De-crystallization treatment:
[0036] The titanium plate after ion deposition exchange is placed in a muffle furnace and de-crystallized in an air atmosphere, thereby completing the in-situ construction of a wide-band wavelength visible / ultraviolet light titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide dual heterostructure on the titanium surface.
[0037] This embodiment constructs a heterostructure to solve the problem of TiO 2 The problem of high recombination rate of photogenerated electron-hole pairs is solved, and the separation of electron-hole pairs is promoted. At the same time, the Z-type heterostructure not only separates the photogenerated electrons and holes, but also makes the oxidation potential of the photogenerated holes more negative and the reduction potential of the photogenerated electrons more positive, thereby achieving a wide range of light absorption spectra. 0.23 TiO 2 , WO 3 and TiO 2 The energy band structures are well matched and have good coupling, and combined with the specific flower-like morphology of this embodiment, a dual heterostructure of titanium dioxide / sodium titanate and / titanium dioxide@tungsten trioxide with excellent photocatalytic effect in the visible light and ultraviolet light wavelength bands is realized.
[0038] The beneficial effects of this embodiment are:
[0039] The present embodiment aims to prepare in situ titanium dioxide / sodium titanate and / titanium dioxide@tungsten trioxide dual structures with excellent photocatalytic effects in the visible and ultraviolet wavelength bands on the titanium plate surface. A porous coating is prepared on the titanium plate surface by micro-arc oxidation technology, and then microwave hydrothermal treatment is performed to form a large number of sodium titanate nanowires (Na2O3) on the titanium micro-arc oxidation coating surface. + +TiO 2 +OH - ―Na 0.23 TiO 2 ), providing more active sites for the subsequent deposition of tungstate ions; and then transformed into a composite structure of titanate and tungstate through ion deposition exchange technology, and then transformed into TiO 2 / WO 3 Heterogeneous structure; at the same time, the process parameters of ion exchange are controlled to retain the structure of sodium titanate nanowires and form TiO 2 / Na 0.23 TiO 2 Heterogeneous structure, thus achieving wide-range wavelength visible / ultraviolet light high catalytic performance, solving the existing TiO 2 The photocatalytic degradation rate of the photocatalyst is low and the recovery is difficult.
[0040] The sample treated by this embodiment was tested by EDS spectrum. Tungsten was successfully introduced into the sample. The composition mainly consisted of W, Ti, O and Na. After XRD diffraction test, TiO 2 、Na 0.23 TiO 2 and WO 3 Phase. Scanning electron microscopy shows that a large amount of titanium dioxide @ sodium titanate and / titanium dioxide @ tungsten trioxide double heterostructures are formed on the surface. In addition, according to transmission electron microscopy photos, WO 3 Particles and TiO 2 The nanorods have a good coupling relationship. The photocatalytic ability of the sample surface treated by this embodiment is characterized by placing it in a methylene blue solution and irradiating it with a xenon lamp. The degradation rate of the organic dye in the fifth cycle reaches more than 86%, and after 5 cycles of cycle testing, the heterogeneous structure on the scanning electron microscope photo does not change significantly, indicating that the sample obtained by this embodiment has stable and long-term degradation performance.
[0041] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the titanium plate described in step 1 is titanium, titanium alloy, titanium-based medium entropy alloy or titanium-based high entropy alloy. The rest is the same as specific implementation method 1.
[0042] Specific embodiment 3: This embodiment is different from specific embodiment 1 or 2 in that the titanium plate described in step 1 is a medium entropy alloy or high entropy alloy of HCP-Ti type, a medium entropy alloy or high entropy alloy of BCC-Ti type, a medium entropy alloy or high entropy alloy of BCC type, or a medium entropy alloy or high entropy alloy of BCC and HCP dual phase. The rest is the same as specific embodiment 1 or 2.
[0043] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the electrolyte described in step 1 is composed of sodium hexametaphosphate, sodium fluoride, sodium hydroxide and deionized water, and the concentration of sodium hexametaphosphate is 5g / L to 20g / L, the concentration of sodium fluoride is 2g / L to 15g / L, and the concentration of sodium hydroxide is 2g / L to 10g / L. Others are the same as specific embodiments 1 to 3.
[0044] Specific embodiment 5: This embodiment differs from Specific embodiments 1 to 4 in that: in step 1, micro-arc oxidation is performed for 5 min to 40 min under the conditions of a current of 0.2 A to 2.0 A, a pulse frequency of 600 Hz to 1000 Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20° C. to 30° C. The rest is the same as Specific embodiments 1 to 4.
[0045] Specific implementation 6: This implementation is different from specific implementations 1 to 5 in that: the alkali solution in step 2 is sodium hydroxide solution, ammonia solution or potassium hydroxide solution; the concentration of the alkali solution in step 2 is 0.5 mol / L to 5 mol / L. Other aspects are the same as specific implementations 1 to 5.
[0046] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that in step 2, the titanium plate treated with micro-arc oxidation is immersed in an alkaline solution and subjected to microwave hydrothermal treatment for 1 h to 6 h at a power of 400 W to 1000 W and a temperature of 60° C. to 200° C. The rest is the same as specific embodiments 1 to 6.
[0047] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: the tungstate solution described in step 3① is a sodium tungstate solution or a potassium tungstate solution; the concentration of the tungstate solution described in step 3① is 0.1mol / L to 2.0mol / L; the concentration of the hydrochloric acid described in step 3① is 6mol / L to 12mol / L. The rest is the same as specific embodiments 1 to 7.
[0048] Specific embodiment 9: This embodiment differs from Specific embodiments 1 to 8 in that: in step 3①, the titanium plate after microwave hydrothermal treatment is immersed in a tungstate solution at a temperature of 20°C to 37°C for 20min to 60min, and then taken out and immersed in hydrochloric acid at a temperature of 40°C to 80°C for 10s to 30s. The rest is the same as Specific embodiments 1 to 8.
[0049] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that in step 4, the de-crystallization treatment is performed for 1 h to 8 h in an air atmosphere at a temperature of 300° C. to 800° C. The rest is the same as specific embodiments 1 to 9.
[0050] The following examples are used to verify the beneficial effects of the present invention:
[0051] Embodiment 1:
[0052] A method for in-situ construction of wide-band wavelength visible / ultraviolet titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide double heterostructures on a titanium surface, which is carried out in the following steps:
[0053] 1. Micro-arc oxidation treatment:
[0054] The titanium plate with the oxide layer removed was placed in an electrolyte, with the titanium plate with the oxide layer removed as the anode and the stainless steel plate as the cathode. The micro-arc oxidation was carried out for 10 min in a pulse constant current mode under the conditions of a current of 1.2 A, a pulse frequency of 600 Hz, a duty cycle of 8%, and an electrolyte temperature of 20 °C to obtain a titanium plate treated with micro-arc oxidation, namely A / R-TiO 2 ;
[0055] The electrolyte is composed of sodium hexametaphosphate, sodium fluoride, sodium hydroxide and deionized water, and the concentration of sodium hexametaphosphate is 10g / L, the concentration of sodium fluoride is 4g / L, and the concentration of sodium hydroxide is 4g / L;
[0056] The titanium plate is HCP+BCC type titanium, niobium, zirconium and tin;
[0057] 2. Microwave hydrothermal treatment:
[0058] The titanium plate treated by micro-arc oxidation was immersed in an alkaline solution, and subjected to microwave hydrothermal treatment for 2 h at a power of 800 W and a temperature of 200 ° C to obtain a titanium plate treated by microwave hydrothermal treatment, i.e., a titanium dioxide / sodium titanate heterostructure in situ constructed on the titanium surface;
[0059] The alkali solution is a sodium hydroxide solution; the concentration of the alkali solution is 3 mol / L;
[0060] 3. Ion deposition exchange treatment:
[0061] ① Immerse the titanium plate after microwave hydrothermal treatment in a tungstate solution for 30 minutes at a temperature of 25°C, then take it out and immerse it in hydrochloric acid for 30 seconds at a temperature of 50°C, and finally wash it with deionized water;
[0062] The tungstate solution is a sodium tungstate solution; the concentration of the tungstate solution is 0.5 mol / L; the concentration of the hydrochloric acid is 12 mol / L;
[0063] ② Repeat step 3① 10 times, and after drying, obtain the titanium plate after ion deposition exchange;
[0064] 4. De-crystallization treatment:
[0065] The titanium plate after ion deposition exchange was placed in a muffle furnace and decrystallized for 5 hours in an air atmosphere at a temperature of 600°C to obtain a titanium plate with a wide-range wavelength visible / ultraviolet light titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide dual heterostructure constructed in situ on the surface.
[0066] Figure 1 This is a scanning electron microscope image of the titanium dioxide / sodium titanate heterostructure in situ constructed on the titanium surface in step 2 of Example 1. As can be seen from the figure, a large number of rich clustered titanium dioxide / sodium titanate composite structures are formed on the titanium surface, and the diameter of the sodium titanate nanowires is about 50nm and the length is about 200nm.
[0067] Figure 2 This is the EDS spectrum of the in-situ construction of wide-range wavelength visible / ultraviolet light titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures on the titanium surface of Example 1; as can be seen from the figure, tungsten element is successfully introduced into the sample, and the composition is mainly composed of W, Ti, O and Na elements.
[0068] Figure 3 This is the XRD spectrum of the wide-range wavelength visible / ultraviolet titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide dual heterostructures constructed in situ on the titanium surface in Example 1. A is the anatase peak, B is the titanium peak, C is the rutile peak, D is the tungsten oxide peak, and E is the sodium titanate peak. It can be seen from the figure that TiO 2 , WO 3 Xianghe Na 0.23 TiO 2 Mutually.
[0069] Figure 4 This is a scanning electron microscope image of the in-situ construction of wide-range wavelength visible / ultraviolet titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures on the titanium surface in Example 1; Figure 5This is a transmission electron microscope image of the titanium dioxide @ tungsten trioxide heterostructure in the titanium surface in situ construction of wide-range wavelength visible / ultraviolet light titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures in Example 1; Scanning electron microscopy shows that a large number of titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures are formed on the surface. In addition, according to the transmission electron microscope photos, WO 3 Particles and TiO 2 The nanorods have a very good coupling relationship.
[0070] A titanium plate with a size of 6mm×6mm with a wide-band wavelength visible / ultraviolet light in-situ constructed titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide dual heterostructure was placed in 10mL of a methylene blue solution with a concentration of 10mg / mL. The solution and the catalyst were then magnetically stirred in the dark for 30min before illumination to achieve adsorption-desorption equilibrium. The methylene blue solution was then irradiated under a UV lamp (300W xenon lamp) with the lamp located 25cm above the top surface of the solution; each cycle lasted 2 hours, for a total of 5 cycles. After each cycle, the sample was taken out and cleaned, and then put back in for testing. During the test, the concentration was measured once every 30 minutes using a UV-visible spectrometer. After each measurement, the probe solution was returned to the photocatalytic reactor. MB has a maximum absorbance at 664nm, which is used as the wavelength for monitoring MB degradation. Figure 6 This is a graph of the fifth cycle photocatalytic degradation rate of the titanium plate after micro-arc oxidation treatment prepared in step 1 of Example 1 and the titanium surface prepared in step 4 constructed with in situ wide-band wavelength visible / ultraviolet light titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures. Figure 7 This is a scanning photo of the titanium surface in-situ construction of wide-range wavelength visible / ultraviolet light titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructure after 5 cycles of cyclic testing in Example 1. Under the irradiation of a xenon lamp, the degradation rate of organic dyes in the first cycle of the titanium surface in-situ construction of wide-range wavelength visible / ultraviolet light titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructure reached 87%, and the degradation rate of organic dyes in the fifth cycle reached 86.2%. After 5 cycles of cyclic testing, the heterostructure on the scanning electron microscope photo did not change significantly, indicating that the obtained sample has stable and long-term degradation performance.
[0071] Embodiment 2: This embodiment differs from Embodiment 1 in that in step 1, the micro-arc oxidation is performed for 10 minutes under the conditions of a current of 1.5 A, a pulse frequency of 600 Hz, a duty cycle of 8%, and an electrolyte temperature of 20° C. The rest is the same as Embodiment 1.
[0072] The sample treated in this embodiment was tested by EDS spectrum. Tungsten was successfully introduced into the sample. The composition mainly consisted of W, Ti, O and Na. After XRD diffraction test of the sample treated in this embodiment, TiO 2 , WO 3 Xianghe Na 0.23 TiO 2 Phase. Scanning electron microscopy shows that a large number of titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures are formed on the surface. In addition, according to transmission electron microscopy photos, WO 3 Particles and TiO 2 The nanorods have a good coupling relationship. The photocatalytic ability of the sample surface treated in this embodiment is characterized by the same test method as in Example 1. A sample with a size of 6 mm × 6 mm is placed in a methylene blue solution. Under the irradiation of a xenon lamp, the degradation rate of the organic dye reaches 90% in the first cycle and 88% in the fifth cycle. After 5 cycles of cycle testing, the heterogeneous structure on the scanning electron microscope photo does not change significantly, indicating that the obtained sample has stable and long-term degradation performance.
[0073] Embodiment 3: This embodiment is different from Embodiment 1 in that the concentration of the alkali solution in step 2 is 5 mol / L. The rest is the same as Embodiment 1.
[0074] The sample treated in this embodiment was tested by EDS spectrum. Tungsten was successfully introduced into the sample. The composition mainly consisted of W, Ti, O and Na. After XRD diffraction test of the sample treated in this embodiment, TiO 2 , WO 3 Xianghe Na 0.23 TiO 2 Phase. Scanning electron microscopy shows that a large number of titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures are formed on the surface. In addition, according to transmission electron microscopy photos, WO 3 Particles and TiO 2 The nanorods have a good coupling relationship. The photocatalytic ability of the sample surface treated in this embodiment is characterized by the same test method as in Example 1. A sample with a size of 6 mm × 6 mm is placed in a methylene blue solution. Under the irradiation of a xenon lamp, the degradation rate of the organic dye reaches 91% in the first cycle and 90% in the fifth cycle. After 5 cycles of cycle testing, the heterogeneous structure on the scanning electron microscope photo does not change significantly, indicating that the obtained sample has stable and long-term degradation performance.
[0075] Embodiment 4: This embodiment is different from Embodiment 1 in that the concentration of the tungstate solution in step 3① is 1 mol / L. The rest is the same as Embodiment 1.
[0076] The sample treated in this embodiment was tested by EDS spectrum. Tungsten was successfully introduced into the sample. The composition mainly consisted of W, Ti, O and Na. After XRD diffraction test of the sample treated in this embodiment, TiO 2 , WO 3 Xianghe Na 0.23 TiO 2 Phase. Scanning electron microscopy shows that a large number of titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures are formed on the surface. In addition, according to transmission electron microscopy photos, WO 3 Particles and TiO 2 The nanorods have a good coupling relationship. The photocatalytic ability of the sample surface treated in this embodiment is characterized by the same test method as in Example 1. A sample with a size of 6 mm × 6 mm is placed in a methylene blue solution. Under the irradiation of a xenon lamp, the degradation rate of the organic dye reaches 93% in the first cycle and 92% in the fifth cycle. After 5 cycles of cycle testing, the heterogeneous structure on the scanning electron microscope photo does not change significantly, indicating that the obtained sample has stable and long-term degradation performance.
[0077] Embodiment 5: This embodiment is different from Embodiment 1 in that the concentration of hydrochloric acid in step 3① is 8 mol / L. The rest is the same as Embodiment 1.
[0078] The sample treated in this embodiment was tested by EDS spectrum. Tungsten was successfully introduced into the sample. The composition mainly consisted of W, Ti, O and Na. After XRD diffraction test of the sample treated in this embodiment, TiO 2 , WO 3 Xianghe Na 0.23 TiO 2 Phase. Scanning electron microscopy shows that a large number of titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures are formed on the surface. In addition, according to transmission electron microscopy photos, WO 3 Particles and TiO 2The nanorods have a good coupling relationship. The photocatalytic ability of the sample surface treated in this embodiment is characterized by the same test method as in Example 1. A sample with a size of 6 mm × 6 mm is placed in a methylene blue solution. Under the irradiation of a xenon lamp, the degradation rate of the organic dye reaches 88% in the first cycle and 86% in the fifth cycle. After 5 cycles of cycle testing, the heterogeneous structure on the scanning electron microscope photo does not change significantly, indicating that the obtained sample has stable and long-term degradation performance.
[0079] Embodiment 6: This embodiment is different from Embodiment 1 in that: Step 4 is performed in an air atmosphere at a temperature of 800° C. The rest is the same as Embodiment 1.
[0080] The sample treated in this embodiment was tested by EDS spectrum. Tungsten was successfully introduced into the sample. The composition mainly consisted of W, Ti, O and Na. After XRD diffraction test of the sample treated in this embodiment, TiO 2 , WO 3 Xianghe Na 0.23 TiO 2 Phase. Scanning electron microscopy shows that a large number of titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures are formed on the surface. In addition, according to transmission electron microscopy photos, WO 3 Particles and TiO 2 The nanorods have a good coupling relationship. The photocatalytic ability of the sample surface treated in this embodiment is characterized by the same test method as in Example 1. A sample with a size of 6 mm × 6 mm is placed in a methylene blue solution. Under the irradiation of a xenon lamp, the degradation rate of the organic dye reaches 92% in the first cycle and 90% in the fifth cycle. After 5 cycles of cycle testing, the heterogeneous structure on the scanning electron microscope photo does not change significantly, indicating that the obtained sample has stable and long-term degradation performance.
[0081] Embodiment 7: This embodiment differs from Embodiment 1 in that the de-crystallization treatment in step 4 is performed for 8 hours. The rest is the same as Embodiment 1.
[0082] The sample treated in this embodiment was tested by EDS spectrum. Tungsten was successfully introduced into the sample. The composition mainly consisted of W, Ti, O and Na. After XRD diffraction test of the sample treated in this embodiment, TiO 2 , WO 3 Xianghe Na 0.23 TiO 2Phase. Scanning electron microscopy shows that a large number of titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures are formed on the surface. In addition, according to transmission electron microscopy photos, WO 3 Particles and TiO 2 The nanorods have a good coupling relationship. The photocatalytic ability of the sample surface treated in this embodiment is characterized by the same test method as in Example 1. A sample with a size of 6 mm × 6 mm is placed in a methylene blue solution. Under the irradiation of a xenon lamp, the degradation rate of the organic dye reaches 95% in the first cycle and 92% in the fifth cycle. After five cycles of cyclic testing, the heterogeneous structure on the scanning electron microscope photo does not change significantly, indicating that the obtained sample has stable and long-term degradation performance.
Claims
1. A method for in-situ construction of wide-band wavelength visible / ultraviolet titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide dual heterostructures on titanium surface, characterized in that It is carried out in the following steps:
1. Micro-arc oxidation treatment: The titanium plate with the oxide layer removed is placed in an electrolyte, with the titanium plate with the oxide layer removed as an anode and the stainless steel plate as a cathode, and micro-arc oxidation is performed in a pulse constant current mode under the conditions of a current of 0.2A to 2.0A, a pulse frequency of 600Hz to 1000Hz, a duty cycle of 4% to 20%, and an electrolyte temperature of 20°C to 30°C to obtain a titanium plate treated with micro-arc oxidation; The electrolyte is composed of phosphate, fluoride salt, alkali solution and deionized water; 2. Microwave hydrothermal treatment: The titanium plate treated by micro-arc oxidation is immersed in an alkali solution for microwave hydrothermal treatment to obtain a titanium plate treated by microwave hydrothermal treatment; 3. Ion deposition exchange treatment: ① Immerse the titanium plate after microwave hydrothermal treatment in a tungstate solution, take it out and immerse it in hydrochloric acid, and finally wash it; ② Repeat step 3① for 5 to 20 times, and obtain the titanium plate after ion deposition and exchange after drying; 4. De-crystallization treatment: The titanium plate after ion deposition exchange is placed in a muffle furnace and de-crystallized in an air atmosphere, thereby completing the in-situ construction of a wide-band wavelength visible / ultraviolet light titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide dual heterostructure on the titanium surface.
2. The method for in-situ construction of wide-band wavelength visible / ultraviolet titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide double heterostructures on a titanium surface according to claim 1, characterized in that The titanium plate described in step 1 is titanium, titanium alloy, titanium-based medium entropy alloy or titanium-based high entropy alloy.
3. The method for in-situ construction of wide-band wavelength visible / ultraviolet titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide dual heterostructures on a titanium surface according to claim 1, characterized in that The titanium plate described in step 1 is a medium entropy alloy or high entropy alloy of HCP-Ti type, a medium entropy alloy or high entropy alloy of BCC-Ti type, a medium entropy alloy or high entropy alloy of BCC type, or a medium entropy alloy or high entropy alloy of BCC and HCP dual phases.
4. The method for in-situ construction of wide-band wavelength visible / ultraviolet titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide dual heterostructures on a titanium surface according to claim 1, characterized in that The electrolyte described in step one is composed of sodium hexametaphosphate, sodium fluoride, sodium hydroxide and deionized water, and the concentration of sodium hexametaphosphate is 5g / L to 20g / L, the concentration of sodium fluoride is 2g / L to 15g / L, and the concentration of sodium hydroxide is 2g / L to 10g / L.
5. The method for in-situ construction of wide-band wavelength visible / ultraviolet titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide dual heterostructures on a titanium surface according to claim 1, characterized in that In step 1, micro-arc oxidation is performed for 5 min to 40 min under the conditions of a current of 0.2 A to 2.0 A, a pulse frequency of 600 Hz to 1000 Hz, a duty cycle of 4% to 20% and an electrolyte temperature of 20° C. to 30° C.
6. The method for in-situ construction of wide-band wavelength visible / ultraviolet titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide dual heterostructures on a titanium surface according to claim 1, characterized in that The alkali solution described in step 2 is sodium hydroxide solution, ammonia solution or potassium hydroxide solution; the concentration of the alkali solution described in step 2 is 0.5 mol / L to 5 mol / L.
7. The method for in-situ construction of wide-band wavelength visible / ultraviolet titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide double heterostructures on a titanium surface according to claim 1, characterized in that In step 2, the titanium plate treated with micro-arc oxidation is immersed in an alkaline solution, and subjected to microwave hydrothermal treatment for 1 h to 6 h at a power of 400 W to 1000 W and a temperature of 60° C. to 200° C.
8. The method for in-situ construction of wide-range wavelength visible / ultraviolet titanium dioxide@sodium titanate and titanium dioxide@tungsten trioxide dual heterostructures on a titanium surface according to claim 1, characterized in that The tungstate solution described in step 3① is a sodium tungstate solution or a potassium tungstate solution; the concentration of the tungstate solution described in step 3① is 0.1mol / L~2.0mol / L; the concentration of the hydrochloric acid described in step 3① is 6mol / L~12mol / L.
9. The method for in-situ construction of wide-range wavelength visible / ultraviolet titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide dual heterostructures on a titanium surface according to claim 1, characterized in that In step 3①, the titanium plate after microwave hydrothermal treatment is immersed in a tungstate solution at a temperature of 20°C to 37°C for 20min to 60min, taken out and then immersed in hydrochloric acid at a temperature of 40°C to 80°C for 10s to 30s.
10. The method for in-situ construction of wide-range wavelength visible / ultraviolet titanium dioxide @ sodium titanate and titanium dioxide @ tungsten trioxide double heterostructures on a titanium surface according to claim 1, characterized in that In step 4, de-crystallization treatment is performed in an air atmosphere at a temperature of 300° C. to 800° C. for 1 h to 8 h.
Citation Information
Patent Citations
Titanium dioxide nanosheet grafted titanium dioxide nanorod heterojunction composite material
CN104941617A
Method for loading metal clusters on photocatalyst
CN114042451A
Heterojunction photocatalyst and preparation method thereof
CN115501869A
Process of preparing rutile and spindle shape titanium dioxide and titanium dioxide using this
KR102121416B1